Prevalence and Risk Factors of Type 2 Diabetes Mellitus in Urban and Rural Population of Kanpur - Pal, Vikas; Nigam, Seema; Barman, Santosh Kumar; Midha, Tanu; Varma, Punit; Kaur, Samarjeet (Indian Journal of Community Health, 2025)
Background: The rising trend of diabetes in populations is due to automation and specific risk factors that may contribute to the development of Type 2 Diabetes Mellitus (T2DM). 90-95% of people with T2DM.The present study assessed the prevalence and risk factors of T2DM in Kanpur's urban and rural populations. Aim & Objective: To determine the prevalence and risk factors of Type 2 diabetes mellitus in urban and rural populations of Kanpur Nagar. Setting &Design: A community based cross-sectional study. Methods & Materials: The study included adults aged 20 years and older. pre-designed, pretested questionnaire covering socio-demographic information, lifestyle, and anthropometry. Random blood sugar (RBS) test to screen for diabetes. Statistical analysis was conducted using SPSS, version 29.0.2.0(20). Results: Diabetes prevalence was 13% overall, with 17.6% in urban areas and 9.2% in rural areas. In both settings, a significant association of diabetes with physical activity, smoking, alcohol consumption, BMI (? 25), weight-height ratio (WHtR), waist-hip ratio (WHR), and a family history of diabetes was seen. Conclusions: Diabetes prevalence is higher in urban than rural areas. Early detection and assessment of high-risk individuals in both regions can help prevent or delay diabetes mellitus and its complications.